2004
DOI: 10.1089/jop.2004.20.548
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-Induced Stimulation of Corneal Wound Healing is a Pure Pharmacological Effect

Abstract: The aim of this study was to evaluate whether corneal reparative activity of hyaluronan is a concentration-dependent phenomenon. Corneal blocks from rabbit eyes were cultured for 20 hours with hyaluronan in different concentrations and molecular weight ranges. In another experiment, the corneal epithelium was denuded and hyaluronan was administered as eye drops. Distances of epithelial migration increased over exposed stroma proportionally to concentration, when hyaluronan was added with a molecular weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 11 publications
3
28
0
5
Order By: Relevance
“…Sodium chloride, thanks to its osmotic power, allows water transfer from stroma to tears, and improve transiently corneal hydration state. Sodium hyaluronate has a protective and healing effect on corneal epithelium and allows a better local tolerance of the treatment [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium chloride, thanks to its osmotic power, allows water transfer from stroma to tears, and improve transiently corneal hydration state. Sodium hyaluronate has a protective and healing effect on corneal epithelium and allows a better local tolerance of the treatment [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that HA/high‐K artificial tears can promote corneal epithelial wound healing in the mechanical scraping model and 0.3 per cent HA/high‐K tears had a better, although statistically non‐significant, effect than 0.15 per cent HA/high‐K tears. In previous studies, Camillieri and colleagues investigated the effect of topical hyaluronic acid solution in the rabbit model of mechanical abrasion and they found that 0.2 and 0.4 per cent hyaluronic acid solutions promoted corneal epithelial wound healing. Another study by Yang and colleagues also demonstrated the therapeutic effect of one per cent cross‐linked hyaluronan gel in a rabbit model of mechanical abrasion.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the therapeutic effect of topical hyaluronic acid has been determined in vivo . Different formulations of hyaluronic acid, such as 1.0 to 2.0 per cent hyaluronic acid gel, 0.1 to 0.4 per cent hyaluronic acid eye drops and cross‐linked hyaluronic acid gel, have been tested in previous studies and found to enhance corneal epithelial wound healing in animal models …”
mentioning
confidence: 99%
“…Auch Hyaluronsäure wirkt mukoadhäsiv, viskoelastisch, zytoprotektiv und wundheilungsfördernd. So vermag auch Hyaluronsäure die toxischen BAC-Wirkungen zu vermindern [3,19,20]. Die subjektiven und objektiven Parameter sind bei Anwendung dieses Polymers besser als bei unpolaren Polymeren [17,21].…”
Section: Therapeutic Strategies In Dry Eye Disease -A Survey Of Possiunclassified